Pengaruh Kualitas Produk Dan Kualitas Pelayanan Terhadap Keputusan Pembelian Pada Urban Seaside Restauran & Bar Nusa Dua Badung Bali (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2026)
Purchasing decisions are used as part of the main factors that determine the level of success of a business activity and also provide support in winning the competition in this industrial world. This study was conducted with the aim of determining the effect of product quality and service quality on purchasing decisions at Urban Seaside Restaurant & Bar Nusa Dua Badung Bali. The population that supports this study is consumers who visit Urban Seaside Restaurant & Bar Nusa Dua with a total of 130 people. The number of sample data used was 130 respondents, where the calculation of this sample applied the infinite method and accidental sampling method. Data collection was carried out by conducting interviews, observations and questionnaires. Data were analyzed by conducting research instrument tests, classical assumption tests, multiple linear regression analysis, coefficient of determination and t-tests and also including the F test. This study provides results by proving that product quality and service quality provide results with evidence of a positive influence and also a significant direction partially and simultaneously on purchasing decisions at Urban Seaside Restaurant & Bar Nusa Dua. The resulting R² coefficient reached 54.5%, thus providing evidence that product quality and service quality contribute to purchasing decisions at Urban Seaside Restaurant & Bar Nusa Dua. It is recommended that Urban Seaside needs to improve food storage and presentation as well as service efficiency, while further research is recommended to explore different locations and additional variables.